Cystic Adventitial Disease of the Common Femoral Vein: A Case Report and Review of the Literature. (October 2013) - Mousa, Albeir Y.; Alhalbouni, Saadi; Abu-Halimah, Shadi; Gill, Gurpreet; Sadek, Betro; Nanjundappa, Aravinda; Hass, Stephen M.; AbuRahma, Ali F.
We report on a 52-year-old female patient who presented with a 6-month history of right lower extremity swelling and tenderness. The patient was treated as an outpatient with full anticoagulation, without any improvement. Her medical history was significant for hypertension and high cholesterol, and she had a full coagulopathy profile that was negative for any hypercoagulable syndrome. On examination, the patient was moderately obese, with significant tenderness over the medial aspect of the right groin. A venous duplex examination revealed hypoechoic structure ± acute deep vein thrombosis of right common femoral vein (CFV). A computed tomography of the venous phase revealed an eccentric compression over the medial wall of the right CFV. During surgical exploration, adventitial cystic mucinous disease was enucleated from the medial wall of the right CFV, and the pathological examination confirmed the diagnosis. The postoperative course was uneventful, and all swelling and tenderness were completely resolved. The patient continued to do well, and she had an unremarkable venous duplex evaluation at her 6-month follow-up.